QSPR Study on Enhanced Resonance Light Scattering of Dye-Human Serum Albumin - Li, Y.K. (Asian Journal of Chemistry, 2013)
Quantitative structure-property relationships models of correlating structure information of dye molecule, with enhanced resonance light scattering intensity and the maximum resonance light scattering wavelength of dye-human serum albumin aggregation were established respectively by partial least squares regression method. The results show that the quantitative relationship models with good fitness and strong predicting power are obtained on small number of sample sets. Also the primary structural parameters of dye molecule affecting the enhanced resonance light scattering intensity and resonance light scattering wavelength were respectively selected and verified.